Penatalaksanaan Hipokasifikasi Email Dengan Restorasi Komposit Kelas IV Pada Gigi Anterior Rahang Atas - Diani Prisinda; Cindy Lestari Marshaliana (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
The advances in restorative materials and adhesive technology plays an important role in dentistry. Adhesive system is currently the main choice for shifting in the principle of “extension for prevention” to “minimally invasive”. In this case, composite resin restorations class IV discoloration accompanied by hypocalcification circumstances was found. Class IV restoration is the restoration of the anterior teeth interproximal surfaces that involve the incisal edge of the tooth, while enamel hypocalcification is opaque white patches on the surface of the email that usually occurs due shortly matrix enamel hypomineralization and is often found in the maxillary incisor teeth. Restoration of class IV composite in this case was done by preparation minimally invasive techniques incremental in filling composite resin, estethic contouring with the use of composite tints and opaquers, as well as finishing and polishing both showed satisfactory results with minimal cost when compared to the restoration of full crown.